Outbreak of acute larval cyathostominosis – A "perfect storm" of inflammation and dysbiosis. (6th October 2020) - Walshe, Nicola; Mulcahy, Grace; Crispie, Fiona; Cabrera‐Rubio, Raul; Cotter, Paul; Jahns, Hanne; Duggan, Vivienne
Abstract: Background: Cyathostomins are prevalent and pathogenic intestinal helminths of horses, causing acute and chronic disease, including acute larval cyathostominosis, which has a mortality rate of 50%. Factors determining individual susceptibility to acute larval cyathostominosis are unknown. Investigation of these factors could lead to novel treatment and prevention strategies. Objectives: To investigate clinicopathological and faecal microbiota changes associated with disease in individual horses in an acute larval cyathostominosis outbreak. Study design: Case series. Methods: The study population was a herd of 23 mixed breed horses in Ireland. The outbreak occurred in November 2018. Fourteen horses were clinically affected. Clinical status was monitored and recorded. Blood and faecal sampling allowed clinicopathological, faecal 16s rRNA gene sequencing and faecal egg count analyses. Results: Two horses were euthanised, whilst 12 recovered. Common clinical signs included loose faecal consistency, weight loss and pyrexia. Consistent clinicopathological findings were borderline anaemia, leucocytosis, thrombocytosis, hyperfibrinogenaemia, hyperglobulinaemia and a reverse A: G ratio. Decreased alpha‐diversity of the faecal microbiota and greater relative abundance of the genus Streptococcus, class Bacilli, order Lactobacillales and family Streptococcaceae, and family Prevotelleceae was found in clinically affected horses compared to their clinically normal cohorts. An increase in obligate fibrolytic bacteria was seen in the clinically normal group compared to the clinical group. Histopathological findings of the colon and caecum revealed a severe necrotising typhlocolitis associated with cyathostomin larvae and bacterial overgrowth in the mucosa of the large intestine. Main limitations: The study population in this outbreak is small. There are several confounding factors limiting this to a descriptive case series. Faecal microbiota has been shown to reflect the large intestinal microbiota but do not represent changes directly. Conclusions: These findings suggest that acute larval cyathostominosis is associated with dysbiosis of the gut microbiota as well as the inflammatory stimulus of numerous emerging larvae leading to structural and functional pathology of the large intestine.